The good pirates of the forgotten bayous : fighting to save a way of life in the wake of Hurricane Katrina - Wells, Ken (Yale University Press, 2008)
With a long and colorful family history of defying storms, the seafaring Robin cousins of St. Bernard Parish, Louisiana, make a fateful decision to ride out Hurricane Katrina on their hand-built fishing boats in a sheltered Civil War-era harbor called Violet Canal. But when Violet is overrun by killer surges, the Robins must summon all their courage, seamanship, and cunning to save themselves and the scores of others suddenly cast into their care. In this gripping saga, Louisiana native Ken Wells provides a close-up look at the harrowing experiences in the backwaters of New Orleans during and after Katrina. Focusing on the plight of the intrepid Robin family, whose members trace their local roots to before the American Revolution, Wells recounts the landfall of the storm and the tumultuous seventy-two hours afterward, when the Robins' beloved bayou country lay catastrophically flooded and all but forgotten by outside authorities as the world focused its attention on New Orleans. Wells follows his characters for more than two years as they strive, amid mind-boggling wreckage and governmental fecklessness, to rebuild their shattered lives. This is a story about the deep longing for home and a proud bayou people's love of the fertile but imperiled low country that has nourished them.